Raising and Educating Children in a Roma Family to Practice their Faith Through Roma Customs - Budayová, Zuzana; Roubalová, Marie; Martin, José Garcia; Grežo, Henrich; Cilingiri, Julinda (Journal of Education Culture and Society, 2023)
Aim. The main aim of the paper is to highlight the education of children in Roma families to practice their faith through Roma customs. The authors identify the practice of faith in Roma holidays which are baptism, sacrament of Eucharist and Confirmation, funeral. Methods. The authors use the literary-descriptive method which they use for analytical-synthetic gathering of professional and scientific knowledge. They overlap these with the practical field empirical experience of the authors dealing with the issue. Results. The Roma family is a patriarchal constitution ensuring the transmission of the cultural and customary heritage of the Roma. Through education by imitation, children learn through the customs and habits of their relatives to observe and practice the faith, thus ensuring the continuation of the family line in a living faith. Conclusion. The Roma have adopted majority Christianity in Slovakia as their own. However, Roma groups retain their customs and rituals, which they have incorporated into their religion and practice of faith. For the Roma, religion and its association with customs and traditions is a connection to God. Therefore, these rituals need to be observed in order to be handed down to the next generation.